LEVEL OF KNOWLEDGE OF FLOOD AND LANDSLIDE DISASTER MITIGATION FOR STUDENTS IN PUBLIC JUNIOR HIGH SCHOOLS - MGB, A. ilmadana; Deprian, Ivmal; Anisa, Anisa; Ramlah, Ramlah; Fadly, Ftrya L; Tomsio, Ismail; Adriansyah, Adriansyah; Yusneti, Yusneti; Hariyadi, Eko (Geographica: Science and Education Journal, 2024)
Floods and landslides are one of the many main problems faced in Indonesia, including in Southeast Sulawesi, which has a major impact on the lives of its people. In dealing with floods and landslides, mitigation knowledge is needed as an effort to recognize the risk of floods and landslides, as well as how to deal with them. This study aims to evaluate the level of knowledge of grade VIII students of SMPN 01 Wundulako, Kolaka Regency related to flood and landslide disaster mitigation. Through research using a quantitative approach to disaster education, students are equipped with an understanding of the causes, impacts, and mitigation actions of disasters. The results of the study show that the percentage of students' knowledge about flood disaster mitigation, which is 79.7%, is in the high category, and the percentage of students' knowledge level about landslide disaster mitigation, which is 89%, is in the very high category, so that the average of the overall data is 84.4%. Knowledge about disaster mitigation needs to be improved through learning programs that are structured, interactive, and in accordance with students' level of understanding. This step is expected to be able to create a generation that is more aware and ready to face potential disasters in the future.